2007
DOI: 10.2146/ajhp060062
|View full text |Cite
|
Sign up to set email alerts
|

Stability of total nutrient admixtures with lipid injectable emulsions in glass versus plastic packaging

Abstract: Certain lipid injectable emulsions packaged in plastic containers have baseline abnormal GSD profiles compared with those packaged in glass containers. When used to compound TNAs, the abnormal profile worsens and produces less stable TNAs than those compounded with lipid injectable emulsions packaged in glass containers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 14 publications
2
33
2
Order By: Relevance
“…In fact, the newly adopted USP monograph titled "Lipid Injectable Emulsion" 32 specifies a pH range between 6.0 and 9.0, yet not one of the neonatal TNAs fell within this range. In fact, acidic TNAs (pH < 6.0) are commonly found in many such admixtures in adults, 4,33 in addition to the more profound pH levels seen in neonatal TNAs here and previously. 25 Moreover, it is not advisable to attempt to elevate the final pH of PN formulations, as admixtures with pH >6.4 carry a high risk of producing potential harmful calcium-phosphate incompatibilities.…”
Section: Discussionsupporting
confidence: 60%
“…In fact, the newly adopted USP monograph titled "Lipid Injectable Emulsion" 32 specifies a pH range between 6.0 and 9.0, yet not one of the neonatal TNAs fell within this range. In fact, acidic TNAs (pH < 6.0) are commonly found in many such admixtures in adults, 4,33 in addition to the more profound pH levels seen in neonatal TNAs here and previously. 25 Moreover, it is not advisable to attempt to elevate the final pH of PN formulations, as admixtures with pH >6.4 carry a high risk of producing potential harmful calcium-phosphate incompatibilities.…”
Section: Discussionsupporting
confidence: 60%
“…1 This upper limit takes into account both emulsion stability issues and probable occurrence of embolic occlusions. 29,30 In this regard, Driscoll et al 31,32 recently reported that native lipid emulsions packaged in plastic containers and exceeding the PFAT 5 limit produce less-stable total nutrient admixtures compared with those packaged in conventional glass, which do meet proposed USP standards.…”
Section: Resultsmentioning
confidence: 99%
“…3,6 We have also shown that the lipid formulations exceeding the PFAT 5 limits of USP chapter 729 not only contain an inordinate number of potentially embolic fat globules but that such coarsening of the GSD has also been associated with instability when used under two common clinical conditions: (1) TNAs 6 and (2) aseptic transfer of native 20% emulsion to a syringe for delivery in critically ill premature infants. 7 In this present study, a third common clinical use condition of lipids for parenteral nutrition support as delivered via 3CP bags was investigated.…”
mentioning
confidence: 93%